THE EURASIAN UNION OR THE EUROPEAN UNION? A DILEMMA FOR THE EASTERN PARTNERSHIP COUNTRIES - VILPIŠAUSKAS, RAMŪNAS (Politologija, 2013)
The author analyzes the Eurasian Customs Union, the motives for its creation, its impact on Russia, Kazakhstan, and Belarus as well as the perspectives for the further integration of its member states to establish the Eurasian Economic Union. It is argued that the creation of the Eurasian Customs Union is based mostly on the foreign trade policy measures applied by Russia and adopted by the other members of the Union. The Eurasian Union and its institutions such as the Eurasian Economic Commission and Court are seen as agents of the member states, especially Russia, rather than independent supranational actors acting in of the Union’s interests. The Eurasian Union represents a regional entity which is both being modelled on the EU and is intended to provide a competing center of attraction for third countries. The establishment of the Eurasian Customs Union has changed the geopolitical situation in the EU eastern neighborhood by creating an alternative option of regional integration for the EU Eastern Partnership countries. For Ukraine and other countries of the Eastern Partnership, which declare their intention to sign association and deep and comprehensive free trade agreements with the EU, joining the Eurasian Customs Union would imply that the EU will have to negotiate agreements on trade with the Eurasian Union rather than with individual countries. This would significantly postpone the prospects of integration of these countries into the EU. The eastern partners of the EU, therefore, have to choose between two alternatives of integration (and Belarus has already chosen the eastern direction). Meanwhile, the EU has to rethink its own policy towards the Eastern Partnership countries and offer incentives for the further reforms to advance trade liberalization and association with the EU without damaging its own credibility. This is the key issue for the Lithuania’s EU Council Presidency forthcoming in the second half of 2013.